Service provision in the wake of a new funding model for community pharmacy - Alesha J. Smith; Shane L. Scahill; Jeff Harrison; Tilley Carroll; Natalie J. Medlicott (BMC, 2018)
Abstract Background Recently, New Zealand has taken a system wide approach providing the biggest reform to New Zealand community pharmacy for 70 years with the aim of providing more clinically orientated patient centred services through a new funding model. The aim of this study was to understand the types of services offered in New Zealand community pharmacies since introduction of the new funding model, what the barriers are to providing these services. Method A survey of all community pharmacies were undertaken between August, 2014 and February, 2015. Basic descriptive statistics were completed and group comparisons were made using the chi squared test with significance set at p < 0.05. Results 528 responses were received. Education and advice on prescription and non-prescription medicines were the two top listed services provided. There were no significant differences in service provision between rural and metro based pharmacies. Many pharmacies were considering introducing new patient centred services. Four of the top ten frequently provided services have no public funding attached. Costs and staff availability are the most common barriers to undertake services, more predominantly in patient centred services. Conclusion This study was the first to provide an evaluation of service provision in response to a new funding model for New Zealand Community Pharmacies. A broad range of services are being undertaken in New Zealand community pharmacies including patient-centred services. A number of barriers to service provision were identified. This study provides a baseline for the current levels of service provision upon which future studies can compare to and evaluate any changes in service provision with differing funding models going forward.